Law applicable to international contracts in the history of the conflict of laws - Carrascosa González, Javier (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
This study aims to unveil the keys of the law applicable to international contracts in history. From Antiquity and the Dark Ages to the 21st century. Connecting factors such as the place of celebration of the contract, the place of performance of the obligations arising from the contract, the choice of law agreement, the habitual residence of the contracting party who must perform the characteristic performance and the closest links clause have been considerated for different reasons. In this paper, the contributions of great legal scholars experts in private international law, such as Bartholo da Sassoferrato, Rochus Curtius, Charles Dumoulin, F.K. von Savigny and especially Jacobo de las Leyes, are present. This work argues, contrary to the Marxist view of the history and the law, that the progress of private international law is due to individuals, with names and surnames, genuine geniuses of private international law.